Analysis Learning Management System in vocational education. Issue 2 (March 2021) - Lasmanawati, E; Muktiarni, M; Maosul, A
Abstract: The development of e-learning is developing because of the demands of learning methods that require innovation in improving learning, so that students are not bored and not monotonous in the learning process. Therefore it is applied or the emergence of various learning systems based on e-learning which is one of the learning models that supports learning based with information technology (IT). The purpose of this study is to analyse and compare several Learning Management Systems (LMS) in the scope of vocational education. LMS is a software application for online activities, electronic learning programs (e-learning programs) and training content. With the advent of various e-learning systems one of them is LMS. Learning Management System is expected to make students more independent, creative and facilitate the implementation of learning that can be done anywhere and anytime. In addition, online learning also makes it easy to control student assignments. LMS has the scope of administration, delivery of material, assessment, monitoring, and communication. Materials in pedagogic and professional competencies, which are made with multimedia packaging (text, animation, video, sound) in the LMS will accelerate (accelerate) mastery of science and technology.